2007
DOI: 10.1186/1471-2105-8-188
|View full text |Cite
|
Sign up to set email alerts
|

Identifying regulatory targets of cell cycle transcription factors using gene expression and ChIP-chip data

Abstract: Background: ChIP-chip data, which indicate binding of transcription factors (TFs) to DNA regions in vivo, are widely used to reconstruct transcriptional regulatory networks. However, the binding of a TF to a gene does not necessarily imply regulation. Thus, it is important to develop methods to identify regulatory targets of TFs from ChIP-chip data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 41 publications
1
44
0
1
Order By: Relevance
“…It has been shown that TF binding usually affects gene expression in a nonlinear fashion: below some level it has no effect, while above a certain level the effect may become saturated [29,30]. Thus, the regulation function z j [ t ] was modeled as the sigmoid function, which is one kind of Hill function, of y j [ t ] (the protein activity profiles of transcription factor j ) [3,16,30-33]…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that TF binding usually affects gene expression in a nonlinear fashion: below some level it has no effect, while above a certain level the effect may become saturated [29,30]. Thus, the regulation function z j [ t ] was modeled as the sigmoid function, which is one kind of Hill function, of y j [ t ] (the protein activity profiles of transcription factor j ) [3,16,30-33]…”
Section: Resultsmentioning
confidence: 99%
“…In patients with chronic illnesses, depression may occur due to adverse circumstances including loss of role in the workplace and family, decreased mobility, decreased physical and cognitive competence and loss of sexual function [1]. Elevated proinflammatory cytokines in patients with chronic illness may be a product of the disease itself and associations between elevated cytokine levels and increased depression among patients with chronic medical illnesses may, in fact, be unrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is the most common psychological problem encountered among patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) [1, 2], and is associated with increased morbidity and mortality in these patients [3]. Depressive disorders and medical illnesses are linked by several mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…To identify the intercellular PPIs between pathogen and host during infection of zebrafish with C. albicans , we utilized the Temporal Relationship Identification Algorithm (TRIA), which uses gene expression data to identify a given transcription factor's regulatory targets from its binding targets as inferred from ChIP-chip data [22]. The first step was to build a pool of C. albicans cell surface proteins.…”
Section: Methodsmentioning
confidence: 99%